Trigonometry (11th Edition) Clone

Published by Pearson
ISBN 10: 978-0-13-421743-7
ISBN 13: 978-0-13421-743-7

Chapter 6 - Inverse Circular Functions and Trigonometric Equations - Section 6.4 Equations Involving Inverse Trigonometric Functions - 6.4 Exercises - Page 287: 51c


$\alpha = arctan(\frac{x~tan~\beta}{x+y})$

Work Step by Step

From the diagram: $tan~\alpha = \frac{x}{z}$ $z = \frac{x}{tan~\alpha}$ $tan~\beta = \frac{x+y}{z}$ $z = \frac{x+y}{tan~\beta}$ We can equate the two expressions for $z$: $\frac{x}{tan~\alpha} = \frac{x+y}{tan~\beta}$ $\frac{tan~\alpha}{tan~\beta} = \frac{x}{x+y}$ We can solve this equation for $\alpha$: $\frac{tan~\alpha}{tan~\beta} = \frac{x}{x+y}$ $tan~\alpha = \frac{x~tan~\beta}{x+y}$ $\alpha = arctan(\frac{x~tan~\beta}{x+y})$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.